Digital photography improves estimates of dietary intake in adolescents with intellectual and developmental disabilities. Issue 1 (January 2015) - Ptomey, Lauren T.; Willis, Erik A.; Goetz, Jeannine R.; Lee, Jaehoon; Sullivan, Debra K.; Donnelly, Joseph E.
Abstract: Background: Dietary assessment of adolescents with intellectual and developmental disabilities (IDD) is challenging due to the limited cognitive abilities of this population. Objective: The purpose of this study was to determine the feasibility of using of digital images to improve the estimates of energy and macronutrient intake from proxy-assisted 3-day food records in adolescents with IDD. Method: Participants used a mobile device to take photos of all food and beverages consumed over a three-day period and simultaneously completed a standard parent-assisted 3-day food record at two separate time points. A registered dietitian reviewed and recorded the differences between the standard record and the images. The proxy-assisted records and the photo-assisted records were analyzed separately. Results: One hundred and thirty eating occasions were entered (20 participants (age = 14.9 ± 2.2 yrs, 45.0% female)). Photo-assisted records captured significantly higher estimates of energy intake per eating occasion than regular proxy-assisted records ( P = 0.001) as well as significantly greater grams of fat ( P = 0.011), carbohydrates ( P = 0.003), and protein ( P = 0.004). Conclusion: The use of photo-assisted diet records appears to be a feasible method to obtain substantial additional details about dietary intake that consequently may improve the overall estimates of energy and macronutrient intake when using proxy-assisted diet records in adolescents with IDD.